LITERACY VALUE OF SURAT AL-'ALAQ VERSES 1–5 IN TAFSIR AL-MISHBAH AND ITS IMPLEMENTATION IN MADRASAH - Akhmad Makhfud; Abdul Khamid; Ruwandi Ruwandi (Universitas Muhammadiyah Metro, 2021)
It is so important to read that Allah SWT sent down His revelations to the Prophet Muhammad SAW. the first is the command to read in the letter al-'Alaq verses 1-5. This study aims to: (1) To describe the concept of literacy value of surat al-'Alaq verses 1-5 in Tafsir al-Mishbah. (2) To describe the implementation of the literacy value of Surat al-'Alaq verses 1-5 in Tafsir al-Mishbah at MTs Al Uswah Kec. Bergas, Kab. Semarang in 2021. This type of research includes the type of library research, which is research that studies and explores various written sources related to the theme carried by the author, namely the literacy value of the letter al-'Alaq verses 1–5 and its implementation at the madrasah tsanawiyah school level by making M. Quraish Shihab's Tafsīr al-Mishbah as the main source of reference. While the nature of this research is descriptive analytical in this study the subject is in the form of the Literacy Value of Surat al-'Alaq verses 1–5 in Al-Mishbah Tafsir and Its Implementation at MTs Al Uswah Kec. Bergas, Kab. Semarang will be discussed in a clear, coherent and directed manner. Based on the results of the analysis of the book Tafsir al-Mishba h and research at MTs Al Uswah Kec. Bergas, Kab. Semarang shows that: (1) the book Tafsir al-Mishbah is a book of Tafsir al-Qur'an by Prof. Dr. Quraish Shihab, which the book uses the method of tafsir tahlili (analytic), which is a method of interpreting the Koran which intends to explain the contents of the verses of the Koran from all its aspects and follow the order of the verses and surats that have been arranged in the mushaf the Koran now. In the systematic writing of Tafsir al-Mishbah, Quraish Shihab begins by explaining the meaning of the word of Allah SWT in a language that can be understood by many people, conditioned by the cultural environment and the development of science today. (2) The literacy value in Q.S. al-’Alaq verses 1-5 according to the Tafsir Al-Mishbah consist of four aspects of value, namely reading, research, writing, and teaching values. (3) Regarding the implementation of literacy values in order to increase reading interest among students, the head of MTs Al-Uswah Kec. Bergas, Semarang District implements a policy on the morning literacy movement program.Keywords: Tafsir Al-Misbah, Literacy Value, Implementation Tafsir Al-Misbah